Serum Kulit Manggis Dan Beras Putih Sebagai Antiaging Dan Brightening - Agus Susanti; Vira Alya Hermawan (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
Skincare are very important for facial care. There are various skin problems one of which is premature aging and dull skin. The perpose of the writer is to know and explain the process making mangosteen skin serum and white rice as anti-aging and brightening, to find out and explain the benefits of mangosteen skin and white rice as anti-aging and brightening and to explain the public acceptance of the mangosteen skin serum and the white rice as anti-aging and brightening. the methoud used is observation, documentation, experiment, interview, questionares and literature. The third experiment produced the composition are 2ml glyserin, 1,5ml mangosteen extract, 1,5ml white rice extract, 5ml aquades, 0,5ml phenoxythanol, 1gr allantoin and 0,5g hydroxtethyl cellulose. Gives off the color beige, nice smell, thick texture and a moist application. After 14 times use, the face will feel moist, bright and fine line and wrikles on the faces are camouflaged. Based on public trials, the average output of 30 panels is the third product with an average of 3,43. The second product has an average of 3,26 and the first product hasan average of 2,93. Thus, it can be concluded that products could be the innovation of problems of premature aging and dull skin